SISTEM KEAMANAN PADA KUNCI PINTU RUMAH SMART KEY MENGGUNAKAN QUICK RESPONSE (QR) BARCODE - Nureza Ardina, Elfira; Erlinasari; Dwi Cahyono, Taufiq (Journal of Computer Science and Technology (JCS-TECH), 2024)
The conventional house door security system is a security system that still uses metal keys and door handles. This conventional house door security system has weaknesses in its security system, because this conventional security system can be duplicated such as doubling for a key. Keys that can be duplicated make conventional door lock security systems have weaknesses. For a home security system that is more sophisticated and high for the level of security, the door lock security system technology is made based on a smart key using the Quick Response (QR) Barcode on the homeowner's smartphone. This research is to provide smart key technology using Quick Response (QR) Barcodes in the homeowner's smartphone and assist homeowners in accessing the data of anyone who opens the door of the house. The method used a system that will be built to make these tools and programs, then test the smart key tool for the house door lock and the Quick Response (QR) Barcode tool on the homeowner's smartphone. The results of research conducted to obtain system accuracy and security on smart key technology using Quick Response (QR) Barcodes on smartphones.